Cambridge Corpus Christi College 201 as a Mirror for a Prince? Apollonius of Tyre, Archbishop Wulfstan and King Cnut - Atherton, M (Taylor and Francis (Routledge), 2016)
This article analyses the composition and contents of CCCC 201, a manuscript containing a substantial collection of the writings of the writer and statesman Archbishop Wulfstan, as well as, among other prose texts, the first romance in the English language, Apollonius of Tyre (it is arguably also significant as being the ‘fifth’ codex of Old English poetry, since it contains Judgement Day II and four other poems). Building on earlier scholarship I argue for substantial connections between the social and political themes of the two main narrative prose texts – the Old English Apollonius of Tyre and the Story of Joseph – and the rest of the anthology. Written in the mid-eleventh century, most likely at the New Minster in Winchester, the manuscript presents a coherent grand narrative of law-making and nation-building that connects the book with the court of King Cnut.